Effects of forest type on carbon storage in the hilly region of Loess Plateau, China - Song, Zhihua; Shi, Peng; Li, Peng; Li, Zhanbin; Niu, Hongbo; Zu, Pengju; Cao, Manhong; Jia, Yili (Frontiers in Forests and Global Change, 2024)
The hilly region of the Loess Plateau has lush vegetation and high carbon sequestration potential. However, previous studies have not focused on differences in carbon storage of different forest types and their causes. This study aimed to explore the carbon storage of forest and identify the main influencing factors of carbon storage to provide basis for improving the carbon fixation capacity of planted forest in the region. Broad-leaved, coniferous, and mixed forests at different altitudes were selected from the Ziwuling Mountains in the Loess hilly region. The carbon storage as well as physical and chemical characteristics of the vegetation and soil samples from different soil layers were measured. The vegetation factor, terrain factor, and soil factor of the sample plot were evaluated by Mantel test and redundancy analysis (RDA). The carbon storage of the mixed forest (138.87 MgC hm−2) showed the highest carbon storage compared to broad-leaved forest (131.97 MgC hm−2) and coniferous forest (113.62 MgC hm−2) in the loess hilly region. The carbon storage of different components followed the order of soil carbon storage, vegetation carbon storage, and litter carbon storage. The soil organic carbon content and forest type had the highest explanations for total carbon storage, accounting for 57 and 26.9% of the variance, respectively. This indicates that forest type is an important factor affecting carbon storage, and selecting mixed forests can achieve better results when creating and transforming carbon sink forests.